Competitiveness in Emerging Markets Market Dynamics in the Age of Disruptive Technologies (Contributions to Management Science,, 2018)
This book presents a collection of interrelated research advances in the field of technological entrepreneurship from the perspective of competition in emerging markets. Featuring contributions by scholars from different fields of interest, it provides a mix of theoretical developments, insights and research methods used to uncover the unexplored aspects of competitiveness in emerging markets in an age characterized by disruptive technologies.